Developing a GeoGebra-Based Teaching Module on Quadrilateral Area and Perimeter to Enhance Seventh-Grade Students' Critical Thinking Skills - Husnuz Zaimah; Tatag Yuli Eko Siswono; Tri Dyah Prastiti (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Seventh-grade students often need help to grasp the concepts of area and perimeter, particularly when applied to real-world problems requiring critical thinking. This difficulty highlights a need for engaging and effective teaching resources beyond traditional methods. Method: This study employed a Research and Development (R&D) approach using the ADDIE model to design, develop, and evaluate a GeoGebra-based teaching module explicitly targeting the area and perimeter of quadrilaterals. The module, designed to foster critical thinking, underwent rigorous validation by media and material experts before being tested for practicality and effectiveness with seventh-grade students. Result: The GeoGebra-based teaching module was valid and practical, receiving high scores from expert evaluations and user feedback. More importantly, the module's implementation positively impacted students' critical thinking skills related to area and perimeter, as evidenced by significant improvement between their pre-intervention and post-intervention assessments. Novelty: This study provides valuable evidence for the efficacy of GeoGebra-based teaching modules in significantly improving critical thinking skills within a specific mathematical context. It addresses a critical gap in existing educational resources by offering a validated, practical, and effective tool that can be adapted to elevate mathematical understanding and cognitive skills in middle school education